"Discoursing sectarianism" approach: What and how to analyse in sectarian discourses. (12th April 2022) - Alghashian, Abdulaziz; Menshawy, Mustafa
Abstract: This article puts forth 'discoursing sectarianism' as an approach helping overcome gaps in essentialism, instrumentalism and constructivism as the three main lines of analysing sectarianism. The approach takes language as a point of departure, showing how it can dually describe reality as a 'neutral' medium of communication and also create reality as constitutive component of practices sectarianisation. The approach also focuses on workings of ideology and power relations as part of linking language, texted in variable formats such as written speeches, monuments or images, with contexts shaping or being shaped with them. Thus, we have to study manifestations or articulations sectarianism, e.g. a speech or an image, within the broader process of their actualisation or materialisation (e.g. the context in which these articulations are enforced, transformed, challenged or falsified). This broader process of discoursing sectarianism within language and beyond can thus accommodate elements predominating analyses in the three other lines of enquiry such as religion and history. The final section of the paper maps a practical and analytical toolkit for researchers and analysts seeking to investigate sectarian discourses by offering the three mutually inclusive levels of textual practices, discursive practices and political practices.